2015
DOI: 10.1039/c4nr05893c
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surface roughness on substrate-tuned gold nanoparticle gap plasmon resonances

Abstract: ARTICLE This journal isThe effect of nanoscale surface roughness on the surface plasmon resonance of gold nanoparticles on thermally evaporated gold films is investigated experimentally and numerically. Single-particle scattering spectra obtained from 80 nm diameter gold particles on a gold film show significant particle-to-particle variation of the peak scattering wavelength of ±28 nm. The experimental results are compared with numerical simulations of gold nanoparticles positioned on representative rough gol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 20 publications
2
32
0
Order By: Relevance
“…20,21 Recent publications have reported on the important role of surface roughness on the far-and near-field as well as nonlinear optical properties of nanoparticles. [22][23][24][25] In an experiment published in 2012, 26 it was shown that the resonance of a film-coupled nanoparticle system undergoes a shift that cannot be explained by a simple local constitutive relation between the electric field E and the polarization P of a metal: a more complex, nonlocal , 27 relation accounting for electron-electron interactions had to be considered in order to…”
mentioning
confidence: 99%
“…20,21 Recent publications have reported on the important role of surface roughness on the far-and near-field as well as nonlinear optical properties of nanoparticles. [22][23][24][25] In an experiment published in 2012, 26 it was shown that the resonance of a film-coupled nanoparticle system undergoes a shift that cannot be explained by a simple local constitutive relation between the electric field E and the polarization P of a metal: a more complex, nonlocal , 27 relation accounting for electron-electron interactions had to be considered in order to…”
mentioning
confidence: 99%
“…Other groups have suggested that nanoparticle size distribution, 28,44 presence of facets, 28,39,44 variations in the nanoparticle−film gap distance, 27,29−32,34−36 and Au film roughness 45 are likely contributors to the particle-to-particle variability observed in single NPoF systems. The variability in the vertical antenna mode that we find is however less than the variability reported in the literature.…”
Section: Articlementioning
confidence: 99%
“…2,3 That is an optoelectronic device that absorbs light with a certain wavelength region and generates electron-hole pairs, and then produces an electrical signal due to separation and directional movement of the electron-hole pairs. [5][6][7] Gold nanoparticle (AuNP), a nanostructure of three-dimensional submicrometre-size of gold atoms with unique physical and chemical properties different from those of the bulk state or atoms, [8][9][10] has recently attracted significant interest in photoelectric applications for realizing, for example, optically switchable transistors, 5,11 photovoltaic cells, 12,13 light-emitting diodes, 14 surface plasmonic devices 7,9,15,16 and photodetectors [17][18][19] due to the quantum size effect resulting in specific electronic structures. For example, broadband photodetectors could be loaded in spectrometric analyzer so that one photodetector can detect light from ultraviolet, visible, to infrared.…”
Section: Introductionmentioning
confidence: 99%